Water and Los Angeles: A Tale of Three Rivers, 1900-1941 - Deverell, William (University of California Press, 2016)
Los Angeles rose to significance in the first half of the twentieth century by way of its complex relationship to three rivers: the Los Angeles, the Owens, and the Colorado. The remarkable urban and suburban trajectory of southern California since then cannot be fully understood without reference to the ways in which each of these three river systems came to be connected to the future of the metropolitan region. This history of growth must be understood in full consideration of all three rivers and the challenges and opportunities they presented to those who would come to make Los Angeles a global power. Full of primary sources and original documents, Water and Los Angeles will be of interest to both students of Los Angeles and general readers interested in the origins of the city.